If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-8/7=1
We simplify the equation to the form, which is simple to understand
3x-8/7=1
Simplifying:
3x-1.14285714286=1
We move all terms containing x to the left and all other terms to the right.
+3x=+1+1.14285714286
We simplify left and right side of the equation.
+3x=+2.14285714286
We divide both sides of the equation by 3 to get x.
x=0.714285714287
| 5x-8=13+7(x+12) | | -7(2x-4)=-14 | | 11/7=y/10 | | 1-(x-2)=-3 | | -4(v-1)=-2v-4 | | (-3/8-2/3)-(-9/8-3/1) | | 9=9x+7/4+7x+3/2 | | n=P*200/R*V | | -2b-3(b+2)=-5(b-6) | | 35x^2+19x+2=0 | | n=R*V/P*200 | | 1=x/27 | | 180d=18 | | 3(u-3)-5=-4(-4u+5)-u | | 2k^2-9k+9=0 | | 6r-10=-4(r-5) | | -6x-35=10-3x | | n=P*V/R*200 | | (-9/2)^2 | | -2(3x-2)+x+9whenx=-3 | | 5(3x-1)=-1x-7 | | 3y-6+2/6=5 | | -3X^2+12X+36=0 | | -61=-25-4x | | 9x+11=11x-11 | | (14x-10)=(11x+5) | | -9x+75=-22-4(x+12) | | -4.8=1.2d-2.2 | | 6m-8=2+9m-10 | | (-16)/0.25 | | X^2+12X+36=4X^2 | | X^2+2X+36=4X^2 |